RESEPSI PEMBACA PADA SITUS DARING TERHADAP NOVEL YUKIGUNI KARYA KAWABATA YASUNARI - Risman, Yunita El; Utami Arif, Nurwanda (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
Readers play an important role in analyzing a literary work. Each reader gives meaning and response to a work that may be similar but can also differ. Therefore, the existence of various online sites for reviewing a literary work enables other readers to see the diversity of responses to a novel. A Japanese novel that has received considerable attention and appreciation from readers is Yukiguni by Kawabata Yasunari. Various reader perspectives can be found on different online sites or blogs, such as Goodreads.com and LibraryThing.com, or in online bookstores like Amazon.co.jp. This study uses a descriptive qualitative approach to identify reader responses on online sites and analyzes them structurally. Through literary reception studies, it can be observed that each reader has a unique perspective on literature. Literary reception research also shows that literature is not static but is continuously brought to life and renewed by readers with each reading. This enriches literary studies by emphasizing the dialogical aspect between text and reader. The results of this study reveal readers' synchronous comments on the intrinsic elements of the novel which receive appreciation from readers in terms of both praise and criticism.